Design and Implementation of Bionic Ankle Joint and its Cable Drive Mechanism - Qian Lei; Li Yihao; Wang Caidong; Chen Lumin; Wang Xinjie (Jixie chuandong, 2016)
A bionic device for the ankle,which has shaft non-perpendicular is designed in according to the structure characteristics of human physiological ankle. The device is consist of three degrees of freedoms that the rotating joint of lower leg,ankle joint and subtalar joint. To reduce the quality of ankle,the motors driving the ankle and the subtalar joint are installed on the thigh and transmission through cables,which cross the knee,fixed on the sheave to limit the rotation angle of each joint. The D-H coordinate method is used in coordinate system selection. Through simulation,the motion attitude space of the mechanism is analyzed and calculated,and compared with the related attitude parameters of human foot. It shows that this mechanism can achieve motion features that similar to human physiological ankle joint. This mechanism can be used in the field of humanoid robot,and can also be a reference for the research of the movement characteristic of the human ankle joint.